The dose-response relationship between training load and aerobic fitness in Academy Rugby Union players - Taylor, R. J.; Sanders, D.; Myers, T.; Abt, G.; Taylor, C. A.; Akubat, I. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To identify the dose-response relationship between measures of training load (TL) and changes in aerobic fitness in academy rugby union players. Method: Training data from 10 academy rugby union players were collected during a 6-wk in-season period. Participants completed a lactate-threshold test that was used to assess VO2max, velocity at VO2max, velocity at 2 mmol/L (lactate threshold), and velocity at 4 mmol/L (onset of lactate accumulation; vOBLA) as measures of aerobic fitness. Internal-TL measures calculated were Banister training impulse (bTRIMP), Edwards TRIMP, Lucia TRIMP, individualized TRIMP (iTRIMP), and session RPE (sRPE). External-TL measures calculated were total distance, PlayerLoad™, high-speed distance >15 km/h, very-high-speed distance >18 km/h, and individualized high-speed distance based on each player`s vOBLA. Results: A second-order-regression (quadratic) analysis found that bTRIMP (R2=.78, P=.005) explained 78% of the variance and iTRIMP (R2=.55, P=.063) explained 55% of the variance in changes in VO2max. All other HR-based internal-TL measures and sRPE explained less than 40% of variance with fitness changes. External TL explained less than 42% of variance with fitness changes. Conclusions: In rugby players, bTRIMP and iTRIMP display a curvilinear dose-response relationship with changes in maximal aerobic fitness.